Peningkatan Kompetensi Guru melalui Pendampingan Penyusunan Perencanaan Pembelajaran Berbasis Kurikulum Merdeka - Ismiyati; Bestari Dwi Handayani; Tusyanah; Mar'atus Sholikah Sholikah (Politeknik Piksi Ganesha Indonesia, 2024)
As a result of the implementation of the Independent Curriculum, teachers have difficulty analyzing and interpreting Learning Outcomes into Learning Objectives) and Learning Objectives Flow. On the other hand, the purpose of community service is training in preparing learning plans based on the Independent Curriculum. The target of this service is the representation of teachers in Early Childhood Education at the Raudlatul Athfal Teachers Association, Parakan Temanggung District, totaling thirty (30) people. The method used in this service activity is socialization and training with an educational approach. The result of this activity is that teachers' understanding of the preparation of learning planning based on the Independent Curriculum has increased. In addition, the enthusiasm of the participants was very high because the material delivered was under their needs. As a follow-up plan for the next service activity, participants need scheduled training from the planning stage to its implementation in learning along with assessments in the form of videos and photos.